Exogenous application and interaction of biochar with environmental factors for improving functional diversity of rhizosphere's microbial community and health. (May 2022) - Ren, Tianbao; Feng, Huilin; Xu, Chensheng; Xu, Qian; Fu, Bing; Azwar, Elfina; Wei, Yaowei; Lam, Su Shiung; Liu, Guoshun
Abstract: The usage of fertilizer with high nitrogen content in many countries, as well as its enormous surplus, has a negative impact on the soil ecological environment in agricultural system. This consumption of nitrogen fertilizer can be minimized by applying biochar to maintain the sufficient supply of nitrogen as nutrient to the near-root zone. This study investigated the effects of various amounts of biochar application (450, 900, 1350, and 1800 kg/hm 2 ) and reduction of nitrogen fertilizer amount (10, 15, 20, and 25%) on the nutrients and microorganism community structure in rhizosphere growing tobacco plant. The microorganism community was found essential in improving nitrogen retention. Compared with conventional treatment, an application of biochar in rhizosphere soil increased the content of soil available phosphorus, organic matter and total nitrogen by 21.47%, 26.34%, and 9.52%, respectively. It also increased the abundance of microorganisms that are capable of degrading and utilizing organic matter and cellulose, such as Actinobacteria and Acidobacteria. The relative abundance of Chloroflexi was also increased by 49.67–78.61%, and the Acidobacteria increased by 14.79–39.13%. Overall, the application of biochar with reduced nitrogen fertilizer amount can regulate the rhizosphere microecological environment of tobacco plants and their microbial population structure, thereby promoting soil health for tobacco plant growth while reducing soil acidification and environmental pollution caused by excessive nitrogen fertilizer. Graphical abstract: Image 1 Highlights: Biochar can compensate N2 fertilizer in supplying nutrient to rhizophere soil. Biochar increases organic matter, phosphorus, and nitrogen in rhizophere soil. Biochar favors a healthy rhizosphere microecological environment for plants. Soil microbial diversity is enriched and provides active pool for plant nutrients. Biochar with reduced N2 fertilizer promote soil health with less acidification.